2013
DOI: 10.3390/molecules18044140
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New 2-Azetidinones with Sulfonamide Structures

Abstract: New series of N-(arylidene)hydrazinoacetyl sulfonamides 4a1–6, 4b1–6 and N-(4-aryl-3-chloro-2-oxoazetidin-1-yl)aminoacetyl sulfonamides 5a1–6, 5b1–6 were synthesized. The structures of the new derivatives was confirmed using spectral methods (FT-IR, 1H-NMR, 13C-NMR). The antibacterial activities of these compounds against Gram positive (Staphyloccoccus aureus ATCC 6583, Staphyloccoccus epidermidis ATCC 12228, Enterococcus faecalis ATCC 25912) and Gram negative (Klebsiella pneumoniae CIP 53153, Proteus vulgaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The radical scavenging ability of the chitosan derivatives against 1,1-diphenyl-2-picrylhydrazyl (DPPH) was assessed based on the method described in literature [ 25 , 26 , 27 ] with minor modifications. To 50 µL of stock solution (20 mg/mL in 2% acetic acid) was added 2950 µL of DPPH solution (0.1 nM in methanol).…”
Section: Methodsmentioning
confidence: 99%
“…The radical scavenging ability of the chitosan derivatives against 1,1-diphenyl-2-picrylhydrazyl (DPPH) was assessed based on the method described in literature [ 25 , 26 , 27 ] with minor modifications. To 50 µL of stock solution (20 mg/mL in 2% acetic acid) was added 2950 µL of DPPH solution (0.1 nM in methanol).…”
Section: Methodsmentioning
confidence: 99%
“…The scavenging ability (%) of the complexes was found 69±0.23, for (C1) complexand 80±0.34, for (C2) complex. Comparing the scavenging ability, both complexes are less active than ascorbic acid (97.08±0.52) [50] [51].…”
Section: Dna Cleavagementioning
confidence: 99%
“…Its pharmacokinetic studies have shown that it is suitable for once-a-week dosing, which makes it unique among the other DPP-4 inhibitors. 18,19 In this research we have designed novel 1,2,4-oxadiazole derivatives with sulfonamide and pyrrolidine-2-carbonitrile scaffolds specifically in vitro DPP-IV inhibitor assay as antidiabetic activity. In the continuation of our research to develop small molecules as biologically active antihyperglycaemic compounds, new derivatives having a pyrrolidine-2-carbonitrile-sulfonamide backbone hybrid were designed and synthesized in search for new potent DPP-4 inhibitors as antidiabetic agents.…”
Section: Introductionmentioning
confidence: 99%